Utility of Charge Transfer and Ion-Pair Complexation for Spectrophotometric Determination of Eletriptan Hydrobromide in Pure and Dosage Forms - Ayman A. Gouda; Ragaa El Sheikh; Rham M. El-Azzazy (Journal of Chemistry)
Three simple, sensitive, and accurate spectrophotometric methods have been developed for the determination of eletriptan hydrobromide (ELT) in pure and dosage forms. The first two methods are based on charge transfer complex formation between ELT and chromogenic reagents quinalizarin (Quinz) and alizarin red S (ARS) producing charge transfer complexes which showed an absorption maximum at 569 and 533 nm for Quinz and ARS, respectively. The third method is based on the formation of ion-pair complex between ELT with molybdenum(V)-thiocyanate inorganic complex in hydrochloric acid medium followed by extraction of the colored ion-pair with dichloromethane and measured at 470 nm. Different variables affecting the reactions were studied and optimized. Beer's law is obeyed in the concentration ranges 2.0–18, 1.0–8.0, and 2.0–32 μg mL−1 for Quinz, ARS, and Mo(V)-thiocyanate, respectively. The molar absorptivity, Sandell sensitivity, detection, and quantification limits are also calculated. The correlation coefficients were ≥0.9994 with a relative standard deviation (R.S.D%.) of ≤0.925. The proposed methods were successfully applied for simultaneous determination of ELT in tablets with good accuracy and precision and without interferences from common additives, and the validity is assessed by applying the standard addition technique, which is compared with those obtained using the reported method.